Scaling to new heights: methodological insights for uplifting research on grassroots digital innovation - Paolo Gerli; Fabio Neves da Rocha; Luca Mora (Humanities & Social Sciences Communications)
The Covid-19 pandemic has further evidenced the potential of grassroots actors as initiators of digital innovations, in the form of open-source applications, platform cooperatives, and other crowdsourced digital artifacts. These innovations played a crucial role in mitigating the impact of lockdown measures, specifically serving the needs of communities often neglected by commercial offerings from large tech companies. Grassroots digital innovations (GDIs) have long been recognized by scholars and policymakers as potential remedies to market distortions and social iniquities within digitalization processes. Nevertheless, these initiatives have historically struggled to become sustainable. Recent evidence confirms that many GDIs developed in response to the global health crisis are now facing financial issues that threaten their survival. In this commentary, we reflect on this challenge and assert that GDI literature exhibits several shortcomings that contribute to undermining the long-term stability of these initiatives and their capacity to foster more inclusive, just, and sustainable digitalization processes. We examine how these shortcomings can be addressed to enhance both GDI research and practice. Our discussion focuses on three major methodological and conceptual limitations: a tendency towards theory-devoid empiricism, a bias towards successful cases, and a dearth of longitudinal, multi-site analyses. We discuss the causes of each shortcoming and illustrate how they impact both the theoretical and practical development of GDIs. Drawing on this critical examination, we identify four priorities to advance future GDI research: leveraging methodological pluralism, applying theoretical sampling, enhancing qualitative longitudinal research, and strengthening methods for data collection and archival. These priorities aim to inform the agendas of academic communities, funding bodies, and policy institutions dedicated to harnessing the potential of GDIs for more sustainable and inclusive digitalization processes.